The complete mitochondrial genome of Asian palm civet (Paradoxurus hermaphroditus) with phylogenetic consideration - Vaishnavi Kunteepuram; Ara Sreenivas; Wajeeda Tabasum; Anil K. Challagandla; Ajay Gaur (Mitochondrial DNA. Part B. Resources, 2018)
Asian palm civet (Paradoxurus hermaphroditus) is one of the smallest palm civet which is least studied. Here, we report the first complete mitochondrial (mt) genome of Asian palm civet (P. hermaphroditus). The circular mt genome with a length of 16,706 bp contained 1 control region, 2 rRNAs, 13 protein-coding genes, and 22 tRNAs. Overall base composition of the complete mt DNA was 33.7% A, 30.5% T, 22.9% C, and 12.9% G. All the genes in mt genome of Asian palm civet (P. hermaphroditus) were distributed on the H-strand, except ND6 and eight tRNA genes encoded on the L-strand. Maximum likelihood (ML) and Bayesian inference (BI) methods were used to infer the phylogenetic relationship of P. hermaphroditus. The phylogenetic analysis shows that all species from the family Viverridae cluster together, in which P. hermaphroditus exhibits the closest relationship with P. larvata.